1996
DOI: 10.1002/(sici)1097-0215(19960904)67:5<709::aid-ijc20>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of growth and apoptosis response in PC-3 and LNCAP prostate-cancer cell lines by FAS

Abstract: Upon androgen ablation, androgen-sensitive prostatecancer cells die by apoptosis (programmed cell death) (Isaacs et al., 1992). However, androgen-sensitive tumor cells can become androgen-resistant during the progression of prostate cancer. finally causing the death of patients. Determining the mechanism of the cell death of prostate tumors is a significant issue which could lead to successful therapy of androgenresistant prostate cancer. FasiAPO-1 is a cell-surface protein, a member of the TNF-receptor family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…[24][25][26] Comparing the two delivery vehicles, the PC-3 cells were more effectively transfected by PAMAM dendrimer than by Effectene, whereas Effectene was superior to PAMAM dendrimer as far as LNCaP cells were tested (data not shown). In the following experiments PC-3 and LNCaP cells were transfected by PAMAM dendrimer and Effectene, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…[24][25][26] Comparing the two delivery vehicles, the PC-3 cells were more effectively transfected by PAMAM dendrimer than by Effectene, whereas Effectene was superior to PAMAM dendrimer as far as LNCaP cells were tested (data not shown). In the following experiments PC-3 and LNCaP cells were transfected by PAMAM dendrimer and Effectene, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…[24][25][26] Although agonistic anti-Fas antibodies (eg CH-11) also kill Fas-positive tumor cells, 25,26 25 FasL gene transfer may be more effective in inducing apoptosis in PC cells than do anti-Fas antibodies. Membrane-bound FasL (mFasL) is converted into sFasL through enzymatic cleavage by matrix metalloproteinase-like enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, b 2 m has been shown to be mitogenic to the PC-3 prostate carcinoma cell line and antagonistic to transforming growth factor b1 action (Rawley et al, 1995). While the molecular mechanism of the lack of b 2 m-induced apoptosis in this cell line is unknown, these cells are also resistant to Fas-ligand or TNF-a (Chung et al, 1998;Takeuchi et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The authors of the accompanying report, and others, have shown that prostate cancer cells lines display a wide range of sensitivities to the major ligands which interact with the cognate cell surface receptors, including TNFR1, TRAIL-R1 and TRAIL-R2 and Fas. [6][7][8][9][10] The differences in sensitivity to the ligands has variously been attributed to differences in Bcl-2 levels, 11 differences in IκB and NFκB activation, [12][13][14][15][16] PTEN expression, 17 constitutive activation of the AKT pathway 18 and survivin levels induced through β1-integrin signaling. 19 The authors themselves have previously shown that formation of the TRAIL-DISC in LNCaP cells is androgen dependent.…”
Section: On the Trail Of Cell Death Pathways In Prostate Cancermentioning
confidence: 99%